1999
DOI: 10.1046/j.1523-1755.1999.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 activates MAP kinase in human mesangial cells: A possible role in collagen expression

Abstract: These data indicate that MAP kinase pathways can be activated by TGF-beta1 in mesangial cells and that the ERK MAP kinase plays a role in TGF-beta-stimulated collagen I expression. Because we have shown previously that SMADs mediate TGF-beta1-stimulated collagen I expression, our findings raise the possibility of interactions between the MAP kinase and the SMAD pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
168
3
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 43 publications
12
168
3
3
Order By: Relevance
“…The current paradigm for Smad regulation implicates multiple signaling pathways modulating Smad activity (18,19), as would likely be the case in the diabetic milieu. We previously reported that ERK enhances Smad activity in TGF-␤1 induction of collagen production (20,21). The observations in the present report indicate that, in addition to stimulating TGF-␤1 expression as has previously been reported (48), glucose-stimulated ERK could directly interact with the Smad pathway to enhance responses to TGF-␤1.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The current paradigm for Smad regulation implicates multiple signaling pathways modulating Smad activity (18,19), as would likely be the case in the diabetic milieu. We previously reported that ERK enhances Smad activity in TGF-␤1 induction of collagen production (20,21). The observations in the present report indicate that, in addition to stimulating TGF-␤1 expression as has previously been reported (48), glucose-stimulated ERK could directly interact with the Smad pathway to enhance responses to TGF-␤1.…”
Section: Discussionsupporting
confidence: 86%
“…Human mesangial cells were isolated by differential sieving of minced human renal cortex as described previously and maintained with DMEM/Ham's F12 (glucose 16.5 mM) supplemented with 20% heat-inactivated FBS, glutamine, penicillin/streptomycin, sodium pyruvate, HEPES buffer, and 8 g/ml insulin (20). After 3 d of preconditioning to 6.5 mM glucose at the seventh passage, the cells were then passaged and cultured in DME containing 6.5 or 20 mM glucose for up to 72 h. Mannitol was used as an osmotic control.…”
Section: Cell Culture and Glucose Conditioningmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study we show that an experimental increase in plasma lipids increases CTGF mRNA and protein expression, so we can now include increased plasma FFA concentrations as one of the potential regulators of CTGF expression. There is evidence that CTGF mediates fibrotic changes in atherosclerotic plaques (37), mesangial expansion in models of diabetic nephropathy (38,39), fibrosis induced by cardiac myofibroblasts following myocardial infarction (40), and scleroderma and keloids (41). Of note, CTGF expression is increased in liver from Zucker obese rats in association with lipid abnormalities and fatty liver in this animal model of insulin resistance (36).…”
Section: Subjectmentioning
confidence: 79%